2006
DOI: 10.1007/s00125-006-0471-5
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting insulin dose-dependent defects in activation of atypical protein kinase C and protein kinase B/Akt in muscles of obese diabetic humans

Abstract: Defective PKBbeta activation/phosphorylation, seen on submaximal insulin stimulation in diabetic muscle, may largely reflect impaired activation of insulin signalling factors present in concentrations greater than those needed for full PKB activation/phosphorylation. Defective aPKC activation, seen at all insulin levels, appears to reflect, at least partly, an impaired action of distal factors needed for aPKC activation, or poor aPKC responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…3B, C) compared with the CON trial. To verify this potential additive signaling effect, we measured skeletal muscle AKT Thr^"** phosphorylation because it closely parallels increases in insulin-stimulated glucose uptake after exercise (II) and is an appropriate marker of skeletal muscle insulin signaling (6). We also found that exercise increased AKT Thr""* phosphorylation in human skeletal muscle (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…3B, C) compared with the CON trial. To verify this potential additive signaling effect, we measured skeletal muscle AKT Thr^"** phosphorylation because it closely parallels increases in insulin-stimulated glucose uptake after exercise (II) and is an appropriate marker of skeletal muscle insulin signaling (6). We also found that exercise increased AKT Thr""* phosphorylation in human skeletal muscle (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…We studied five type 2 diabetic patients (four men, one woman; results of aPKC and PKB activation in men and women are indistinguishable [2, 4, 10]), who were free of cardiovascular, renal, neuropathic and other medical problems. Procedures were approved by the Institutional Review Board of the University of South Florida College of Medicine and the Research and Development Committee of the James A. Haley Veterans Hospital, and were in accordance with the Declaration of Helsinki and Good Clinical Practice.…”
Section: Methodsmentioning
confidence: 99%
“…Euglycaemic–hyperinsulinaemic clamp/muscle biopsy studies were conducted after overnight fasting, as described [2, 4, 10]. After anaesthetising with 0.5% lidocaine, the skin was incised and a biopsy of the vastus lateralis muscle was performed with a 14-gauge needle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations